Pengaruh Kualitas Layanan Akuntansi Syariah Terhadap Kepercayaan Nasabah Bank Syariah - Muammar Khaddafi; Rizki Zaskiyah Daulay; Ira Wahyuni; Elke Dwi Soraya; Zuhra Quratul Aini; Faraisha Syahryanna (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to examine the effect of Islamic accounting service quality on customer trust in the context of Islamic banking. This literature study identifies key factors in enhancing customer trust, including transparency of financial statements, compliance with sharia principles, and overall service quality. Using the literature research method, it was found that consistent and shariah-compliant implementation of Islamic accounting plays an important role in enhancing customer trust. Service quality that includes accuracy, transparency, and sharia compliance has a significant impact on customer trust, which in turn affects customer loyalty and the growth of Islamic banks. This research provides insights for Islamic bank management to improve service quality to build customer trust.